Functioning recovery of veterans with PTSD and mTBI after an 8-week comprehensive intervention - Smashna, Олена (Psychosomatic Medicine and General Practice, 2021)
Background. Significant numbers of veterans with mild traumatic brain injury (TBI) and/or post-traumatic stress disorder (PTSD), usually co-morbid, have functional impairments in various areas of life, which significantly complicate the process of their readaptation and resocialization. They experience significant persistent limitations in daily life, including problems with occupational, family, social activities, and self-care due to a combination of emotional, cognitive, and behavioral impairments that should be targets of intervention, including transcranial stimulation and psychotherapy. Aims. To investigate the effectiveness of a complex intervention, namely the combination of a psychotherapy program with transcranial direct current electrical stimulation (tDCS) in the treatment of patients with PTSD and mTBI by assessing their level of functioning. Methods. Examination data of 329 veterans from three clinical groups were analyzed: individuals with PTSD (n=109), mild TBI (n = 112), and with comorbid PTSD+TBI (n=108). All patients received standard therapy as well as psychotherapeutic intervention (a combination of psychoeducation with elements of motivational interviewing and acceptance and commitment therapy for PTSD (ACT) and transcranial direct current electrical stimulation (tDCS). According to the WHODAS 2.0 scale, the level of functioning was determined in six domains: cognition (CW); mobility (MW); self-care ( SW); relationships (RW); daytime activity (LW); social activity (PW); general level of functioning (WHO). A rank correlation was also determined between individual criteria of the CAPS-5 scale and domains of the WHODAS 2.0 test. Results. In patients of all clinical groups, the most pronounced disorders were in the cognitive sphere (CW), the sphere of relationships (RW), social (PW), and daytime activity (LW). The combination of PTSD and TBI was associated with more significant and persistent cognitive impairment, as well as reduced daytime activity. In the majority of respondents, the indicators of all scales of the WHODAS 2.0 methodology at the second examination were significantly lower than at first, which indicated the effectiveness of the therapy. The state of the cognitive sphere turned out to be essential for the effective psychotherapeutic effect on patients both within the PTSD group and with CCM. The connection of separate domains of WHODAS 2.0 with pathological symptoms of PTSD determines the recommendations to increase the duration of the therapeutic program specifically for the group of PTSD. Conclusions. Impairment of functioning in persons with PTSD, TBI, and the combination of these painful conditions is closely related to the presence and expressiveness of PTSD symptoms, which provides the possibility of differentiated targeted therapy for certain clinical groups of patients.